If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=-3/5(m-9)
We simplify the equation to the form, which is simple to understand
3=-3/5(m-9)
Reorder the terms in parentheses
3=+(-0.6m+5.4)
Remove unnecessary parentheses
+3=-0.6m+5.4
We move all terms containing m to the left and all other terms to the right.
+ 0.6m=+5.4-3
We simplify left and right side of the equation.
+ 0.6m=+2.4
We divide both sides of the equation by 00.6 to get m.
m=4
| 3+35x=15x+7 | | 2c-6=4c+4 | | x-(-8)=-32 | | 4v+2-2(-8v-1)=2(v-3) | | X(.75)=3 | | -2+2x=-3+7x | | 45=24(-7X) | | 45=24-7X | | 2=-z/8+13 | | 55-2x=10-7x | | 32-4x=8(-5x-5) | | 24-16x=-12x | | 5p-5=30 | | 2x-9-6x=-7x+5x | | 2x+5=-44-5x | | 6x+9=9x+6 | | =v^2+2v-8 | | -2p-36=-4(-6+8p) | | -4.2=-0.84(m+4) | | -8w+14=0 | | 7y=9x+6 | | x(x-3)=x^2+6x+8 | | 8x-(6x-3)=17 | | 84=-7+7(a+5) | | 1/3(b-3)=6 | | -4v-1=0 | | p^2q^2=36 | | -4*6+6y=-24 | | -5p+20=25 | | 3x^4*2w^4x^5*8w=x | | 1(b-3)=6 | | 3y-12+63=180 |